CHARACTERIZATION OF A LITHIUM FORMATE EPR-DOSIMETRY SYSTEM FOR PROTON RADIATION THERAPY. Issue 1 (9th January 2019) - Costa, T; Adolfsson, E; Fager, M; Lund, E
Abstract: The specific aim for the characterization of the lithium formate dosimetry system is to determine response and stability in a proton beam. The long-term goal for this investigation is an audit system for proton therapy like the end-to-end dose determinations performed for radiotherapy with photons. For a 150-MeV proton beam, the dose response was found to be linear in the dose interval 0–8.8 Gy. The accuracy of dose reconstruction was controlled in a blind test, in which the dose of 6.63 Gy was measured in samples irradiated with a real dose of 6.70 Gy. The stability was determined by irradiations of sets of four dosimeters every week during 1 month and analyzed at the same day thereafter. The fitting of the fading curve was done with a second-order polynomial resulting in a 6.6% lower value compared to the reference after 31 d.